Synergy Role Of Parents And Teachers Towards Learning Achievement At SMK Karya Pembangunan Paron, Ngawi - Fitria M. Suud; Moh. Toriqul Chaer (AIUA Journal of Islamic Education, 2019)
Efforts to improve student achievement in schools, both academic and non-academic, require the synergistic involvement of parents' roles as figures for children and teachers as movers in school. This study aims to determine the role of parents and teachers in improving student learning achievement at SMK Karya Pembangunan Paron, Ngawi. This study used a qualitative approach, the method of data collection obtained by interviews, observations, and documentation studies. The results showed that first, there is a synergistic relationship between the role of parents and teachers on student learning achievement. Parents have an essential and useful role in providing a conducive learning environment and learning tools needed by students. Second, the teacher played the role of duties and responsibilities as a teacher, educator, mentor, and director in motivating students in school. This study recommends the need for a synergistic relationship between parents and teachers, positive communication between the two needs to be built and maintained as an effort to improve achievement and character in students.